Basic english tourism guide to develop english skills communication and improve the job of brigadistas costeros (tour guides) from Salinas Ecuador, during the term march may 2009 - Llangari Morocho, Lupe Mercedez (2009)
The scheme proposed by Army Polytechnic School Language Department to do this project, in fact there are many specifics detail how to develop a research and obtain the results which permit us to complete this successfully. It is important to note that through this project, a Basic English Tourism Guide is proposed in order to develop English Skills Communication and improve the job of tour guides. According to this purpose, the workshops were developed in Salinas City with a study of Brigadistas Costeros (tour guides) of Basic Level, during the term March May 2009. In order to develop this project, various steps help to obtain; first the identification problem, after that it explores the tourism industry and its components, expose the variables, objectives, and give a clear justifications about the research. The theoretical frame has been designed with the help from different sources such as specialized books, magazines, and Internet contents. An important aspect in the project is the methodology applied and it is explained clearly, including detailed information of the instruments used